2021
DOI: 10.1556/2006.2020.00103
|View full text |Cite
|
Sign up to set email alerts
|

A test of the pathway model of problematic smartphone use

Abstract: Background and aimsProblematic smartphone use (PSU) has been described as a growing public health issue. In the current study, we aimed to provide a unique and comprehensive test of the pathway model of PSU. This model posits three distinct developmental pathways leading to PSU: (1) the excessive reassurance pathway, (2) the impulsive pathway and (3) the extraversion pathway.MethodsUndergraduate students (n = 795, 69.8% female, mean age = 23.80 years, sd = 3.02) completed online self-report measures of PSU (ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 79 publications
1
25
0
1
Order By: Relevance
“…Further, Duke and Montag (2017) highlight that a smartphone can become a learned cue related to the aforementioned channels/content and may be sufficient to elicit cue-reactivity on its own. As perhaps the pre-eminent method of accessing the internet today (Montag et al, 2021) and consistent with current research seeking to identify general risk factors that promote smartphone-mediated problematic behaviors (Billieux et al, 2015;Canale et al, 2021), PSU may be the current driving force behind disordered use of the internet but should not be placed in the same category as drug and alcohol use disorders.…”
mentioning
confidence: 80%
“…Further, Duke and Montag (2017) highlight that a smartphone can become a learned cue related to the aforementioned channels/content and may be sufficient to elicit cue-reactivity on its own. As perhaps the pre-eminent method of accessing the internet today (Montag et al, 2021) and consistent with current research seeking to identify general risk factors that promote smartphone-mediated problematic behaviors (Billieux et al, 2015;Canale et al, 2021), PSU may be the current driving force behind disordered use of the internet but should not be placed in the same category as drug and alcohol use disorders.…”
mentioning
confidence: 80%
“…From the framework proposed by Billieux and colleagues [12,15], PSU is described as a multi-faceted phenomenon entailing a variety of dysfunctional manifestations (addictive, antisocial, and dangerous use), each being associated with distinct developmental pathways, including (1) excessive reassurance (e.g. the need to maintain relationships and obtain reassurance from others), ( 2) impulsivity (mainly driven by poor impulse control, which in turn might result in uncontrolled urges and dysregulated use), and (3) extraversion [e.g.…”
Section: Problematic Smartphone Usementioning
confidence: 99%
“…A recent study conducted by Canale et al ( 10 ), which used a Bayesian analyses approach, provided the first comprehensive test of the pathway model of PSU as posited by Billieux et al ( 1 ). The results of the study indicated that each path (i.e., excessive reassurance, impulsive, and extraversion), was associated with distinct psychosocial and psychopathological variables.…”
Section: Introductionmentioning
confidence: 99%